2022
DOI: 10.1002/mgg3.1940
|View full text |Cite
|
Sign up to set email alerts
|

Germline mutations in Chinese ovarian cancer with or without breast cancer

Abstract: Background Ovarian and breast cancers are known to have significant genetic components. Considering the differences in the mutation spectrum across ethnicity, it is important to identify hereditary breast and ovarian cancer (HBOC) genes mutation in Chinese for clinical management. Methods Two cohorts of 451 patients with ovarian cancer only (OV) and 93 patients with both breast and ovarian (BROV) cancers were initially screened for BRCA1, BRCA2, TP53, and PTEN. 109 OV and 43 BROV patients with extensive clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Moreover, figuring out the alterations of BRCA1/2 , especially germline mutation, is an effective way to identify the inherited risk of cancer and take preventive measures. Previous studies showed that about 8.6–24.5 % patients harbored g BRCA1/2 mutations, while 3.7–7.1 % patients presented s BRCA1/2 mutations [ 10 , [31] , [32] , [33] , [34] , [35] ]. Our study excluded the benign mutations and found the frequencies of g/s BRCA1/2 mutation were 18.55 % and 9.68 %.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, figuring out the alterations of BRCA1/2 , especially germline mutation, is an effective way to identify the inherited risk of cancer and take preventive measures. Previous studies showed that about 8.6–24.5 % patients harbored g BRCA1/2 mutations, while 3.7–7.1 % patients presented s BRCA1/2 mutations [ 10 , [31] , [32] , [33] , [34] , [35] ]. Our study excluded the benign mutations and found the frequencies of g/s BRCA1/2 mutation were 18.55 % and 9.68 %.…”
Section: Discussionmentioning
confidence: 99%
“…As highly conserved DNA remodeling enzymes (58)(59)(60), FANCI and FANCM can activate the FA DNA repair pathway to maintain genomic stability. Patients with FA, characterized by the clinically and genetically heterogeneous syndrome of bone marrow failure, are predisposed with a predisposition to cancers (61)(62)(63)(64). Studies have shown that the loss of function of some FA genes (such as BRCA1 and BRCA2) by germline inactivation can result in familial breast cancer predisposition syndromes (65)(66)(67)(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…Following extended screening, mutations in other HBOC genes were identified in an additional 12.8% of the OV cohort and 14% in the BROV cohort. The most commonly mutated genes were MSH2 and PALB2 (Kwong et al, 2022 ). However, PALB2 was rarely encountered (0.21%) among a group of 1421 patients with ovarian cancer (Kotsopoulos et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%